2008
DOI: 10.3174/ajnr.a1301
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Internal Carotid Artery Calcifications: Association with Vascular Risk Factors and Ischemic Cerebrovascular Disease

Abstract: BACKGROUND AND PURPOSE:Atherosclerotic calcifications are present not only in the extracranial carotid bifurcation but also in the intracranial part of the internal carotid artery. We assessed the association between intracranial internal carotid artery calcifications and cardiovascular risk factors in patients with ischemic cerebrovascular disease and the association between calcifications and the presence of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 21 publications
7
72
3
2
Order By: Relevance
“…3,4 To quantify ICAC, we used a semiautomated scoring method, which is described in detail elsewhere. 4,12 In short, all calcifications in the trajectory of the intracranial internal carotid artery were manually delineated in consecutive multidetector CT-slices while making sure that bony structures were not included. Next, the number of pixels >130 Hounsfield units was determined and the calcification volume (mm 3 ) was calculated by multiplying the number of pixels, pixel-size, and the increment.…”
Section: Assessment Of Icacmentioning
confidence: 99%
“…3,4 To quantify ICAC, we used a semiautomated scoring method, which is described in detail elsewhere. 4,12 In short, all calcifications in the trajectory of the intracranial internal carotid artery were manually delineated in consecutive multidetector CT-slices while making sure that bony structures were not included. Next, the number of pixels >130 Hounsfield units was determined and the calcification volume (mm 3 ) was calculated by multiplying the number of pixels, pixel-size, and the increment.…”
Section: Assessment Of Icacmentioning
confidence: 99%
“…Extracranial and intracranial carotid artery calcifications are associated with cardiovascular risk factors and history of stroke. 13,22,23 Furthermore, extracranial carotid artery calcifications are associated with carotid artery stenosis in asymptomatic patients, but in symptomatic patients this association is less clear. [24][25][26] Moreover, calcifications can be assessed easily and quantified at MDCTA, an imaging modality increasingly used in daily clinical work-up of patients with stroke, making them a suitable and robust marker of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the measurements is provided elsewhere. [12][13][14][15] An intraclass correlation coefficient and coefficient of variation for the aortic arch, extracranial and intracranial carotid artery scoring method was assessed in 29 MDCTA examinations based on the ratings of 2 observers. The intraclass correlation coefficient was 1.00 and the coefficient of variation 10% to 11% for all 3 vessel beds.…”
mentioning
confidence: 99%
“…However, the authors also argue that these methods, especially the method described by de Weert et al, 3 are too time consuming and impractical for larger epidemiological studies. From our experience, there is typically less time pressure in epidemiological studies than in clinical practice, and there is more emphasis on the precision of measurements.…”
mentioning
confidence: 99%
“…From our experience, there is typically less time pressure in epidemiological studies than in clinical practice, and there is more emphasis on the precision of measurements. Against this background, we would like to highlight that we quantified ICAC semiautomatedly 3 in a large, prospective population-based sample of >2500 middle-aged and elderly people and found that larger calcification volumes considerably increased the risk of stroke. 4 This quantification strategy was relatively time consuming (≤8 minutes for a 1-mm thin slice protocol) but definitely not insuperable.…”
mentioning
confidence: 99%